The role of mosque committee in empowering mosque’s educational programmes: case study of mosques in Gombak district, Malaysia (peranan ahli jawatankuasa masjid dalam penambahbaikan program pendidikan masjid: kajian kes bagi masjid-masjid di daerah Gombak) - al-Akiti, Muhammad Ayman; Ahmad, Che Mahzan; Mamat, Ismail; Elias@Mayah, Aliza; Mohd Sobri, Mohd Helmi; Borhan, Lihanna; Abdul Jalil, Mohd Noh; Samsudin, Sofiah; Alias, Majdan; Abdul Rahman, Shukran; Abdul Manan, Kamaruzzaman; Ismail, Khamsiah; et al. (International Islamic University Malaysia, 2021)
This article analyses the roles of the mosque committee in enhancing the mosque’s educational programmes in Gombak, Selangor. Gombak as an administrative district that is located inside the hectic and modernized area of Klang Valley is prone to foreign ideologies and socio-cultural issues. This study aims to broaden the understanding of how the mosque committee in Gombak could empower the mosque’s educational programmes in addressing these issues. This study also aims to discover creative improvision that the committee could make in making the mosque’s educational programmes attractive to the surrounding community. This study focuses on the role of the mosque committee in improving their mosque’s educational programmes with a specific case study on selected mosques in the Gombak district. It is a qualitative study that utilizes the deductive and inductive methods derived from surveys collected from Focus-group Discussion (FGD) and literature studies. Recordings from the FGD survey and recent literature studies related to this topic are examined and analysed according to its appropriation. The result indicates the importance of the mosque committee and their significant roles in enhancing the mosque’s educational programmes such as adjusting the curriculum to cater the diversity of people and continuously improvising the lesson through feedback taken from the surrounding community.